2014
DOI: 10.1002/jmri.24827
|View full text |Cite
|
Sign up to set email alerts
|

Does diffusion‐weighted imaging improve therapy response evaluation in patients with hepatocellular carcinoma after radioembolization? comparison of MRI using Gd‐EOB‐DTPA with and without DWI

Abstract: Additional DWI does not substantially improve therapy response evaluation by Gd-EOB MRI in HCC after radioembolization but proved helpful in single cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…DWI is an increasingly used MR technique, which enables the visualization of diffusivity of water molecules, and may provide information regarding the cellular density and properties of the extracellular matrix [21]. All lesions were hyperintense on DWI, and the marked restricted diffusion can raise suspicion for cHCC-CC, which was supported by Potretzke et al [10].…”
Section: Discussionmentioning
confidence: 94%
“…DWI is an increasingly used MR technique, which enables the visualization of diffusivity of water molecules, and may provide information regarding the cellular density and properties of the extracellular matrix [21]. All lesions were hyperintense on DWI, and the marked restricted diffusion can raise suspicion for cHCC-CC, which was supported by Potretzke et al [10].…”
Section: Discussionmentioning
confidence: 94%
“…No statistically significant difference between Gd-MRI, DWI, and the combination of both in terms of diagnostic accuracy was evident. In some cases, however, DWI provided additional information to detect HCC progression, which was missed by Gd-MRI alone [ 37 ].…”
Section: The Value Of Diffusion-weighted Imaging For Locoregional mentioning
confidence: 99%
“…In imaging after radioembolization, some studies of HCC have suggested that the addition of DWI MRI can contribute to the understanding of tumor response to treatment; however, others have found that addition of DWI offers no significant improvement in this evaluation [85,86]. Liver metastases treated with Y-90 therapy have shown decreased metabolic activity on PET scan following treatment, suggesting that PET could potentially be used as a tool in determining tumor response to radioembolization therapy [87][88][89].…”
Section: Transarterial Chemoembolization and Radioembolizationmentioning
confidence: 94%